Development of nanocomposite membranes for dairy wastewater treatment - Sisay Elias Jigar (2023)
A novel photocatalytic nanocomposite membrane was prepared successfully by blending. poly(vinylidene-fluoride) (PVDF) with TiO2, and/or carbon nanotube (CNT), and/or BiVO4 at various ratios in the membrane material via phase inversion method. The prepared membranes were evaluated for model or real dairy wastewater treatment. The membranes were characterized. by several surface characterization methods as SEM, AFM, XRD, and EDX. XRD and SEM measurements revealed that the nanoparticles were present as 200–300 nm-sized aggregates in the membrane, which increased the roughness of composite blended membranes (AFM results). EDX measurements exhibited that the proteins have covered a relatively large area of the pristine PVDF. membrane, resulting in a relatively high N/F ratio. Addition of TiO2, and/or carbon nanotube (CNT), and/or BiVO4 nanoparticles into the PVDF membrane material decreased the contact angle. of membrane surface, thus increased the hydrophilicity of modified blended membranes. In dead end cell BSA filtration experiment, PVDF/TiO2/CNT/BiVO4 nanocomposite blended membrane exhibited a pure water flux up to 150.52 Lm−2 h −1 which is two-fold higher than virgin membrane and a higher bovine serum albumin (BSA) rejection of about 97 %. Based on flux recovery ratio and flux the optimal CNT ratio in the PVDF/TiO2/CNT and BiVO4 in PVDF/TiO2/BiVO4 nanocomposite membrane was 2 % and 50 % respectively. More importantly, the PVDF /TiO2/CNT-BiVO4-50 (PTCB50) (containing 0.48 wt % TiO2, 0.02 wt % CNT and 0.5 wt % BiVO4) and PVDF/TiO2/BiVO4-50 (PTB50) (containing 0.5 wt % TiO2 and 0.5 wt % BiVO4 in PVDF) membrane exhibited a smaller irreversible fouling and a higher flux recovery ratio, revealing that blending with TiO2, and/or CNT, and/or BiVO4 could improve the self-cleaning under visible irradiation and the antifouling properties of PVDF membrane. The application of BPTB50 and B-PTCB50 membranes to treat real dairy wastewater were promising. They exhibited better antifouling and foulant degradation performance as compared to pristine membrane. However, the lower rejection performances of the membranes were due to ability of lactose to pass through the membranes which requires further treatment. Overall, the incorporation of nanoparticles in the polymer matrix enhanced the antifouling and foulant degradation performance. of the photocatalytic nanocomposite membrane to a remarkable extent.